Comparative physiological and metabolic analyzes of two Italian ryegrass (Lolium multiflorum) cultivars with contrasting salinity tolerance. Issue 3 (5th March 2021) - Feng, Qijia; Song, Shurui; Yang, Yong; Amee, Maurice; Chen, Liang; Xie, Yan
Abstract: Italian ryegrass ( Lolium multiflorum ) is a widely cultivated forage with high nutritional value and good palatability. Salinity, however, is a negative factor to lessen output and quality in Italian ryegrass. The aim of this study was to elucidate the salt tolerance mechanism of two Italian ryegrass cultivars, 'Abundant' and 'Angus'. Under hydroponic conditions, two cultivars of Italian ryegrass with different salt tolerance were exposed to 0 and 300 mM NaCl solution for 1 week, respectively. The results showed that salt stress decreased relative growth rate and relative water content, especially in salt‐sensitive 'Angus'. The salt‐tolerant 'Abundant' cultivar alleviated reactive oxygen species (ROS) induced burst and cell damage. However, 'Angus' exhibited a greater activity of superoxide dismutase (SOD) and peroxidase (POD) than 'Abundant'. Additionally, 'Abundant' exhibited higher photosynthetic efficiency than 'Angus' under salt stress condition. Salt treatment significantly increased the Na/K, Na/Mg, and Na/Ca ratios in the leaves and roots of both cultivars, with a pronounced effect in salt‐sensitive 'Angus'. The metabolite analysis of leaf polar extracts revealed 41 salt responsive metabolites in both cultivars, mainly consisting of amino acids, organic acids, fatty acids, and sugars. Following exposure to salt conditions, salt‐sensitive 'Angus' had a higher level of metabolites and more uniquely upregulated metabolites were detected. Based on these findings, we conclude that the 'Abundant' cultivar emerged as a favorite in saline‐alkali soil, while the 'Angus' cultivar is suitable for planting in normal soil. It appears that the high salt tolerance of 'Abundant' is partly to prevent the plant from ionic homeostasis disruption.